Skeptical theism and moral obligation - Maitzen, Stephen (International journal for philosophy of religion, 2009)
Skeptical theism claims that the probability of a perfect God’s existence isn’t at all reduced by our failure to see how such a God could allow the horrific suffering that occurs in our world. Given our finite grasp of the realm of value, skeptical theists argue, it shouldn’t surprise us that we fail to see the reasons that justify God in allowing such suffering, and thus our failure to see those reasons is no evidence against God’s existence or perfection. Critics object that skeptical theism implies a degree of moral skepticism that even skeptical theists will find objectionable and that it undermines moral obligations that even skeptical theists will want to preserve. I discuss a version of the first objection and defend a version of the second.